Desing of wind propellers for horizontal axis - Albadan-Molano, David Esteban; Salamanca-Céspedes, Jorge Enrique; Gallego-Torres, Adriana Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The GEOM research seedbed of the Universidad Distrital Francisco José de Caldas is developing low and medium power wind turbines, and here we present an advance. Wind energy is a very important source of renewable energy and an excellent alternative for the transition to sustainable energy that the world needs. It is known that horizontal axis wind turbines are more efficient energetically, and that the propeller is determinant for this efficiency; therefore, the correct geometric design of the propeller is essential for an optimum wind turbine. This article analyzes the most relevant aspects in the design of a wind propeller, using MATLAB® software to illustrate its behavior, and suggests an ideal airfoil for wind applications.